Comparison the Efficacy of Fluconazole and Terbinafine in Patients with Moderate to Severe Seborrheic Dermatitis - Narges Alizadeh; Hamed Monadi Nori; Javad Golchi; Shahriar S. Eshkevari; Ehsan Kazemnejad; Abbas Darjani (Hindawi Limited, 2014)
Background. Topical agents can be unpleasant due to long-term therapies in patients with moderate to severe seborrheic dermatitis. Systemic antifungal therapy is another alternative in treatment. Aim. This study was conducted to compare the efficacy of oral fluconazole and terbinafine in the treatment of moderate to severe seborrheic dermatitis. Methods. 64 patients with moderate to severe seborrheic dermatitis (SD) were enrolled in a randomized, parallel-group study. One study group took terbinafine 250 mg daily (n=32) and the other one fluconazole 300 mg (n=32) weekly for four weeks. Seborrheic dermatitis area severity index (SDASI) and the intensity of itching were calculated before, at the end of treatment, and two weeks after treatment. Results. Both drugs significantly reduced the severity of seborrheic dermatitis (P<0.001). Multivariate linear regression revealed that efficacy of terbinafine is more than fluconazole (P<0.01, 95% CI (0.63-4.7)). Moreover, each index of SD severity reduced 0.9 times after treatment. (P<0.002, 95% CI (0.8-1.02)). The itching rate significantly diminished (P<0.001); however, there was no difference between these two drugs statistically. Conclusions. Both systemic antifungal therapies may reduce the severity index of SD. However, terbinafine showed more reduction in the intensity of the disease. In other words, the more the primary intensity of the disease is, the more its reduction will be. This trial is resgistered with 201102205871N1.